New genus for a unique species of Indo-West Pacific bryozoan - Tilbrook, Kevin J. (Zootaxa, 2011)
Larval type, larval morphology, ancestrular morphology and colony astogeny have great systematic value in the cheilostomate bryozoans, but for most species these characters are undocumented. Whilst most cheilostomate bryozoan species produce lecithotrophic coronate larvae; a minority of species produce planktotrophic cyphonautes larvae, all belonging to genera within the superfamily Membraniporoidea. Biflustra laboriosa Tilbrook, 2006 nominally belongs to a membraniporid genus whose species are otherwise characterised by having a twinned ancestrula. The production of a single ancestrula from a cyphonautes larva and overall zooidal morphology excludes B. laboriosa from the Membraniporidae and its zooidal characters are alien to any other membraniporoidean genus. Accordingly, Tarsocryptus n. gen. is erected to accommodate it, resulting in the new combination Tarsocryptus laboriosa n. comb. Its reassignment here to the membraniporoidean Electridae is tentative.